The Multi-Functional Role of Urban Sufism in Building Modern Society's Religiosity - Atamimi, Abdul Basit; Sururi, Sofyan (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This research aims to identify the role of Majelis Zikir Az-Zikra for the formation of urban community religiosity. This qualitative research uses descriptive analysis method, primary data in the form of scientific articles and mass media relevant to the subject matter. This research concludes that the Az-Zikra Zikir Assembly is not only a medium for da'wah and dhikr, but has a complex role for the lives of urban communities, such as socio-economic aspects with a religious approach in increasing economic independence. This research confirms that the role of taklim assemblies for urban communities can have a positive impact on the complexity of life needs, not only related to aspects of religiosity.